Ex ante impact assessment of breeding research under risk in agro-climatic zones of Iran - Abyar, Noormohammad; Alibakhshi, Hasan (Frontiers in Environmental Economics, 2025)
IntroductionIn recent years, agricultural research investment has declined in developing countries, for example, Iran, exposing it to significant financing challenges. In this situation, economic policymakers need documentary evidence of its benefits to be persuaded to fund it. Without this evidence, agricultural research will fail to receive sustainable funding support. This research was conducted to assess the economic return of crop breeding research in three agro-climatic zones in Iran that have been broadly divided into 10 different agro-ecological zones according to their similar climate conditions and types of crops grown. In addition to raising awareness, its results can convince the policymaking system to support agricultural research.MethodsThis research was conducted using the economic surplus analysis method under risk conditions in three agro-climatic zones of Iran.Results and discussionBased on the findings, most crop breeding research projects in the three studied zones yield an internal rate of return ranging from 17 to 81% despite the uncertainty and risk in agricultural research and activities. Therefore, using the developed varieties derived from these projects can play an essential role in increasing agricultural production and the supply of strategic agri-products. The evidence emphasizes the need to support and fund agricultural research, especially crop breeding research. However, the results show that returns on breeding research in the studied agro-climatic zones vary, partially due to climatic and weather conditions. For example, the expected average internal rate of return for irrigated wheat breeding research in the three zones is 70.4%, 71.8%, and 57%, respectively, implying that climate and weather conditions affect the economic return of agricultural research.